Integrated management of information inside maintenance processes. From the building registry to BIM systems - Cinzia Talamo (Techne, 2014)
The paper presents objec- tives, methods and results of two researches dealing with the improvement of integrated information management within maintenance processes. Focusing on information needs regarding the last phases of the building process, the two researches draft approaches characterizing a path of progressive improve- ment of strategies for integration: from a building registry, unique for the whole construction process, to an integrated management of the building process with the support of BIM systems.